1993
DOI: 10.1104/pp.101.2.485
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 3-Hydroxy-3-Methylglutaryl Coenzyme A Reductase Activity during Maize Seed Development, Germination, and Seedling Emergence

Abstract: Seed development in maize (Zea mays) can be divided into three phases based upon morphology and regulation of seed storage protein synthesis (Randolph, 1936;Kiesselbach, 1949;Jones and Brenner, 1987; Kriz, 1989;Ober et al., 1991). During embryogenesis, crucial morphological events occur as evidenced by rapid cell growth, mitotic division, and differentiation. During maturation, the embryo and endosperm enlarge through cell expansion, and storage metabolites are synthesized and deposited (Randolph, 1936;Burr an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
19
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Analysis of HMGR activity during maize seed development has shown that levels are high in the endosperm and embryo during stages of rapid mitotic divisions (Moore and Oishi, 1993). Maize endosperm HMGR activity decreases in parallel to mitotic activity (Moore and Oishi, 1993). The restricted expression of the HMGP-GUS fusions in the dividing endosperm cells might reflect a role for HMGR in cell division similar to that previously discussed for the meristematic cells.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Analysis of HMGR activity during maize seed development has shown that levels are high in the endosperm and embryo during stages of rapid mitotic divisions (Moore and Oishi, 1993). Maize endosperm HMGR activity decreases in parallel to mitotic activity (Moore and Oishi, 1993). The restricted expression of the HMGP-GUS fusions in the dividing endosperm cells might reflect a role for HMGR in cell division similar to that previously discussed for the meristematic cells.…”
Section: Discussionmentioning
confidence: 82%
“…Expression of HMGR genes in rapidly dividing tissues has also been reported in other plants (Aoyagi et al, 1993;Cramer et al, 1993;Moore and Oishi, 1993). The expression of HMGP in meristematic tissues might be related primarily to the high rate of sterol biosynthesis required to sustain the active synthesis of membranes in actively dividing cells.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Plant microsomal HMGR has been shown to be regulated by light (Brooker and Russell, 1979;Ji et al, 1992;Moore and Oishi, 1993), phytohormones (Brooker and Russell, 1979;Russell and Davidson, 1982), wounding, fungal infection, and fungal elicitors (Stermer and Bostock, 1987). Results from our studies of HMGR activity during seed development suggest that this enzyme and its regulation are important during seed development.…”
mentioning
confidence: 99%